Effect of ZnO nanoparticles on biodegradation and biotransformation of co-substrate and sulphonated azo dye in anaerobic biological sulfate reduction processes. (April 2016) - Rasool, Kashif; Lee, Dae Sung
Abstract: In recent years, rapid increase of nanomaterial applications exposed the wastewater treatment plants to the new challenges. Potential effects of nanoparticles (NPs) on biological sulfate reduction and dyes biodegradation in biological wastewater treatment systems still need to be investigated. This study explored the effects of zinc oxide nanoparticles (ZnO-NPs) on sulfate reducing bacteria (SRB) culture treating textile wastewater. Batch reactor studies were performed by exposing the mixed SRB culture to different initial ZnO-NPs concentrations. Increasing ZnO-NPs concentrations from 0 to 200 mg l −1 inhibited the reactor performance by decreasing COD, sulfate, and color removal efficiencies from 54.4%, 78.1%, and 95.4% to 30.1%. 44.0%, and 80.0%, respectively. Moreover, dye biotransformation was also adversely affected in the presence of ZnO-NPs as revealed by the increase in total aromatic amines formation and the decrease in activities of various oxido-reductive enzymes such as veratryl alcohol oxidase, lignin peroxidase, and azo reductase. Highlights: Effects of ZnO-NPs on activity of sulfate-reducing bacteria were investigated. ZnO-NPs significantly inhibited biological sulfate reduction and dye degradation. Dye biotransformation was adversely affected in the presence of ZnO-NPs. A decrease in the activities of various oxido-reductive enzymes was observed.